Let's Read Application in the View of Recreational Readers - suud mujizatullah; Ruslin, S. Pd., M. Pd., M. Sc., Ph. D.; Dzakiah, M. Pd (Universitas Muhammadiyah Jember, 2025)
This research investigates the use of the Let's Read application from the perspective of recreational readers, focusing on students from the English study program at UIN Datokarama Palu. The study aims to understand how students define recreational reading, explore their experiences using the application, and identify encountered challenges. Employing a qualitative case study design, the research gathered data through document reviews and semi-structured interviews with five purposively selected participants. Data analysis followed thematic coding framework guided by Miles and Huberman's qualitative data analysis model. Findings revealed that students possess clear conceptual understanding of recreational reading as leisure activity distinct from academic obligations. The Let's Read application was appreciated for its accessibility, offline reading features, and culturally relevant content. Participants reported increased reading frequency and strengthened identity as recreational readers. However, challenges included limited content targeting older readers, technical issues such as unstable connections, and search limitations within the application. The study concludes that while Let's Read significantly supports recreational reading, enhancements in content diversity and user experience are needed to better serve older student readers. The research offers insights for developers, educators, and policymakers seeking to promote digital literacy and reading engagement through mobile applications.